Kampanye Public Relations GTPP 50 Juta Pohon Melalui Instagram @dishut_jabar - Zain, Frieska Chairunnisa; Muhtadi, Asep Saeful; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2020)
This study aims to describe the public relations campaign process carried out by the West Java Forestry Service which was carried out through social media Instagram @dishut_jabar. Researchers describe the campaign process starting from problem identification, planning, to campaign implementation. This study uses the Ostergaard campaign model with constructivism paradigm through qualitative descriptive methods and data collection through in-depth interviews and collected. The results of this study explain that the public relations campaign for planting and maintaining 50 million trees through Instagram @dishut_jabar carried out by the West Java Forestry Service through social media has gone through three main processes. 1) the problem identification process by looking for data and facts in the field 2) the campaign planning process by determining the need for the use of Instagram social media 3) the campaign implementation process which refers to the results of the analysis and the predetermined plan. documentation.